Disease and democracy : the industrialized world faces AIDS - Baldwin, Peter, 1956- (University of California Press ; Milbank Memorial Fund, 2005)
Disease and Democracy is the first comparative analysis of how Western democratic nations have coped with AIDS. Peter Baldwin's exploration of divergent approaches to the epidemic in the United States and several European nations is a springboard for a wide-ranging and sophisticated historical analysis of public health practices and policies. In addition to his comprehensive presentation of information on approaches to AIDS, Baldwin's authoritative book provides a new perspective on our most enduring political dilemma: how to reconcile individual liberty with the safety of the community. Baldw.
Keywords: AIDS (Disease) -- Developed countries.; Democracy.; Acquired Immunodeficiency Syndrome -- prevention & control; Public Health Practice; Democracy; Disease Outbreaks -- history; Sida -- Pays industrialisés.; Démocratie.; democracy.; MEDICAL -- AIDS & HIV.; HEALTH & FITNESS -- Diseases -- AIDS & HIV.; MEDICAL -- Health Policy.; Acquired Immunodeficiency Syndrome -- prevention and control.; Public Health Practice.; Developed Countries.; Disease Outbreaks -- History.; AIDS (Disease); Developed countries; HIV/AIDS.; acquired immune deficiency syndrome.; aids epidemic.; aids.; american government.; cholera.; community safety.; contagious disease.; discrimination.; europe.; european governments.; governments and governing.; health.; historical.; hiv.; human immunodeficiency virus infection.; illness.; immune system.; individual liberty.; institutional memory.; medical conditions.; medicine.; political.; politics.; public health practices.; public healthcare.; social impacts.; united states of america.; western democracy.; Electronic books.